Molecular characterization of enterovirus-A71 in children with acute flaccid paralysis in the Philippines - Lea Necitas Apostol; Hiroyuki Shimizu; Akira Suzuki; Rifqiyah Nur Umami; Maria Melissa Ann Jiao; Amado Tandoc; Mariko Saito; Socorro Lupisan; Hitoshi Oshitani (BMC Infectious Diseases, 2019)
Abstract Background Several inactivated enterovirus-A71 (EV-A71) vaccines are currently licensed in China; however, the development of additional EV-A71 vaccines is ongoing, necessitating extensive analysis of the molecular epidemiology of the virus worldwide. Until 2012, laboratory confirmation of EV-A71 for hand, foot, and mouth disease (HFMD) and other associated diseases had not occurred in the Philippines. Because EV-A71 has been linked with cases of acute flaccid paralysis (AFP), AFP surveillance is one strategy for documenting its possible circulation in the country. To expand current knowledge on EV-A71, molecular epidemiologic analysis and genetic characterization of EV-A71 isolates were performed in this study. Methods A retrospective study was performed to identify and characterize nonpolio enteroviruses (NPEVs) associated with AFP in the Philippines, and nine samples were found to be EV-A71–positive. Following characterization of these EV-A71 isolates, the complete viral protein 1 (VP1) gene was targeted for phylogenetic analysis. Results Nine EV-A71 isolates detected in 2000 (n = 2), 2002 (n = 4), 2005 (n = 2), and 2010 (n = 1) were characterized using molecular methods. Genomic regions spanning the complete VP1 region were amplified and sequenced using specific primers. Phylogenetic analysis of the full-length VP1 region identified all nine EV-A71 Philippine isolates as belonging to the genogroup C lineage, specifically the C2 cluster. The result indicated a genetic linkage with several strains isolated in Japan and Taiwan, suggesting that strains in the C2 cluster identified in the Asia-Pacific region were circulating in the Philippines. Conclusion The study presents the genetic analysis of EV-A71 in the Philippines. Despite some limitations, the study provides additional genetic data on the circulating EV-A71 strains in the Asia-Pacific region, in which information on EV-A71 molecular epidemiology is incomplete. Considering that EV-A71 has a significant public health impact in the region, knowledge of its circulation in each country is important, especially for formulating vaccines covering a wide variety of strains.